The effect of project-based cooperative learning on disability empathy in pre-service early childhood teachers - Choi, Jihye (Edelweiss Applied Science and Technology, 2024)
This study investigated the effect of project-based cooperative learning in an introductory special education class on disability empathy. Disability empathy is an important competency for pre-service teachers who teach children with disabilities. The subjects of this study were 49 university students who were completing a qualification course for pre-service teachers who teach children with disabilities. First, through theoretical learning, interest and understanding of disabled infants and toddlers were raised, and educational program production activities were carried out to increase understanding of disabilities. Project-based cooperative learning was conducted for a total of 30 hours over 15 weeks. As a result of the study, it was found that the disability empathy of pre-service early childhood teachers significantly increased after the implementation of project-based cooperative learning, and the active interaction item score was the highest in the class satisfaction area. As a result, it was found that project-based cooperative learning has a significant effect on pre-service early childhood teachers' disability empathy and promotes active interaction. The significance of this study is that it empirically verified the effect of project-based cooperative learning on preservice teachers’ disability empathy. It is hoped that the results of this study will be used as teacher education materials to improve pre-service teachers’ disability empathy.